Coronary artery bypass graft pseudoaneurysm from saphenous vein graft stent fracture. Issue 6 (June 2017) - Mojadidi, Mohammad Khalid; Smith, Christopher J.; Dibu, George; Mogali, Kiran; Bavry, Anthony A.; Choi, Calvin; Wymer, David C.
Abstract: Saphenous venous graft (SVG) pseudoaneurysms are a rare complication of coronary artery bypass grafting (CABG). An 85-year-old man with CABG and a distal SVG stent presented with dyspnea. Chest computed tomography (CT) revealed a large partially thrombosed pseudoaneurysm at the distal SVG with stent fracture. Endoluminal exclusion of the distal SVG pseudoaneurysm using a covered stent was performed. Follow-up chest CT and angiography showed persistent pseudoaneurysm filling and enlargement. The SVG proximal to the pseudoaneurysm was embolized with coils to reduce rupture risk. Following embolization, the patient's left ventricular ejection fraction was moderately depressed but the patient remained stable and was discharged. <Learning objective: Saphenous venous graft pseudoaneurysms are a rare post-operative complication of coronary artery bypass graft procedures with a risk of impending rupture if left untreated. Fracture of a vein graft stent is an even further unique etiology of pseudoaneurysms. Covered stents are a practical therapeutic option for the treatment of vein graft pseudoaneurysms, especially in high risk patients who are not surgical candidates.>